VIBROACOUSTIC CHARACTERISTICS OF COMPOSITE MATERIALS REINFORCED BY CARBON FIBRES - Irina V. Zlobina; Danila V. Morozov; Sergey P. Pavlov (Вестник Дагестанского государственного технического университета: Технические науки, 2018)
Abstract. Objectives The aim of the research is to study the features of the propagation of mechanical oscillation waves of ultrasonic frequency through composite materials, including those exposed to a microwave electromagnetic field. Methods The propagation of mechanical waves generated by a source of ultrasonic vibrations is investigated in samples of composite materials reinforced by carbon fibres as used in aircraft construction. Results It is established that, when passing through a composite material, the frequency of the waves decreases by almost two orders of magnitude in comparison with the frequency of the driving dynamic force, while the method of laying reinforcing fibres has a significant effect: the greatest decrease in frequency is observed in composites with a quasiisotropic structure. When the oscillations pass directly through the metal surface, the frequency decreases by not more than an order of magnitude. The amplitude values of vibration acceleration increase with decreasing thickness of the samples and exceed by 2-3 times the waves obtained during the control passage through the steel surface of the gear. The sound pressure level changes from 4.1 Pa for samples with a quasi-isotropic structure to 8.4 Pa for samples reinforced with a metal grid. The processing of the investigated materials in a microwave electromagnetic field leads to a change in the character of the passage of the oscillation waves. The average for a specified period of time vibration acceleration value increases slightly (7-9%), while its unevenness decreases significantly (by between 0.2 and 6 times), i.e. vibrations become stable. For some materials (reinforced with a quasi-isotropic and laminated pressed metal mesh), the vibration acceleration values  do not change at all during a cycle. Conclusion  The obtained result can form the basis for developing technologies for creating structures from composite materials with stable vibroacoustic characteristics.